With or without a koinon. The Longue Durée of Two Regional Festivals. I. The Pamboiotia and the Basileia from their Beginnings to the Fourth Century BC - Tufano, Salvatore (Hyperboreus, 2023)
The paper oﬀers the ﬁrst half of a comprehensive historical survey of the two most important Boiotian regional festivals, i.e. the Basileia of Lebadeia, for Zeus Basileus, and the Pamboiotia of Koroneia, for Athena Itonia. The author contends that these festivals had a regional impact and were performed independently of the existence of a federal government in Boiotia. Part I, in particular, addresses the origins of the two festivals and their status in the fourth century BC. Until the end of the ﬁfth century BC (Section 1), the Pamboiotia are not attested with this name, but indirect evidence of literary and archaeological nature suggests that ritual processions and contests were held in Koroneia for Athena Itonia. The Basileia were only established in 371 BC, but in the sixth and the ﬁfth centuries BC Lebadeia gained a wide reputation as an oracular site, also abroad. Section 2 concentrates on the fourth century BC, which marks the actual beginning of the Basileia. The literary and epigraphic evidence of the fourth century BC on this festival is discussed, but needs to be integrated with later sources: this is possible because of the continuity of the Basileia throughout the Hellenistic and the Republican periods. The Basileia were an individual competition and, although Theban in its ﬁrst initiative, the festival became a national venture of the Boiotians. The fourth century BC marks a gap in the extant evidence on the Pamboiotia. The author contends that this was a moment of minor fortune for the festival and that the Basileia, at ﬁrst, substituted the Pamboiotia as an occasion of self-celebration in Boiotia.